Increased in vitro leishmanicidal activity of octyl gallate loaded poly(methyl methacrylate) nanoparticles. (28th May 2019) - Feuser, Paulo Emilio; Tonini, Maiko Luis; Jacques, Amanda Virtuoso; Santos da Silva, Maria Claudia; Steindel, Mario; Sayer, Claudia; Hermes de Araújo, Pedro Henrique
Abstract: The current paucity of effective and affordable drugs for the treatment of leishmaniasis renders the search for new therapeutic alternatives a priority. Gallic acid-related compounds display anti-parasitic activities and their incorporation into drug carrier systems, such as polymeric nanoparticles may be a viable alternative for leishmaniasis treatment. Therefore, this study focused on the synthesis and characterization of octyl gallate (G8) loaded poly(methyl methacrylate) (PMMA) nanoparticles via miniemulsion polymerization in order to increase the leishmanicidal activity of this compound. G8 loaded PMMA nanoparticles presented a spherical morphology with a mean size of 108 nm, a negatively charged surface (−33 ± 5 mV) and high encapsulation efficiency (83% ± 5). Fourier-transform infrared spectroscopy and X-ray diffraction analysis confirmed that G8 was encapsulated in PMMA nanoparticles and presented a biphasic release profile. The G8 loaded PMMA nanoparticles did not present cytotoxic effect on human red blood cells. G8 loaded PMMA nanoparticles displayed a leishmanicidal activity almost three times higher than free G8 while the cytotoxic activity against human THP-1 cells remained unchanged. Graphical Abstract: UF0001